Effect of Workload and Breastfeeding Motivation of Working Mothers - Rachma Anisa Ulya1, Retnayu Pradanie1, Aria Aulia Nastiti1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background : The practice of exclusive breastfeeding in Indonesia still falls short of expectations due to working mothers’ struggle with managing both working outside and household chores. This workload results in mothers experiencing physical and emotional exhaustion and impacts on their motivation to practice exclusive breastfeeding, hence exclusive breastfeeding failure. Objective: To shed light on the relationship between workload and exclusive breastfeeding motivation of working mothers in the working area of the Public Health Center of Bergas District, Semarang Regency. Method: This is a cross-sectional study with a sample of working mothers in the working area of the Public Health Center of Bergas District, Semarang Regency, with babies aged 0–6 months. The sample of 32 respondents was recruited by purposive sampling technique. The data collected were analyzed by Spearman’s rho analysis. The instruments employed in this research were the modified versions of questionnaires from existing literature. Results : The workload of nearly all of the sample (31 respondents, 96.8%) was categorized into Level 2. Besides, the vast majority of the breastfeeding, working mothers in Bergas District (30 people, 93.7%) had strong exclusive breastfeeding motivation. Last but hardly the least, a ?-value of 0.801 (> 0.05) was obtained, suggesting no relationship between workload and exclusive breastfeeding motivation. Conclusion : Workload bore no association with the exclusive breastfeeding motivation of working mothers. Despite the high workload, if the reinforcement system was high, individual motivation would generally remain high.